-5c+4(2c+7)=-43

Simple and best practice solution for -5c+4(2c+7)=-43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5c+4(2c+7)=-43 equation:


Simplifying
-5c + 4(2c + 7) = -43

Reorder the terms:
-5c + 4(7 + 2c) = -43
-5c + (7 * 4 + 2c * 4) = -43
-5c + (28 + 8c) = -43

Reorder the terms:
28 + -5c + 8c = -43

Combine like terms: -5c + 8c = 3c
28 + 3c = -43

Solving
28 + 3c = -43

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-28' to each side of the equation.
28 + -28 + 3c = -43 + -28

Combine like terms: 28 + -28 = 0
0 + 3c = -43 + -28
3c = -43 + -28

Combine like terms: -43 + -28 = -71
3c = -71

Divide each side by '3'.
c = -23.66666667

Simplifying
c = -23.66666667

See similar equations:

| 4x^2+16-32=0 | | -(-x+3)= | | [4(x+5)-8]-[3-4(x-2)]= | | 4=-8v+4(v+5) | | -5-3x-7x=-85 | | 6[1-(-3x-9)]=90x+276 | | 45=3(4+y) | | 0.5y+0.9(y+4)=0.3(12) | | 21-7v=6(3-v) | | 7.5n-4(-3-6.4n)=20+37.1 | | 5m-7n+8m-8n= | | 14x+.11y=.124 | | -3(x+2)=-19.5 | | 9-2k=3 | | 7+6x=-1 | | 0=1a-2 | | 3x+4(-5x-5)=-207 | | P=450+.03+3 | | 1y+-6=4 | | 6x+4y=-15 | | 10/1-2/3=x | | 36x^2-12h+1=0 | | 0=9a-2 | | 8(2n+2)=9(9n+5)+3 | | 22x^9-2x^3= | | Y=2(3.14)x | | -2(n-4)=4(3-2) | | ax+3=8a+b | | 2=5f-3 | | (x+2)(x+3)=x^2+5x+q | | 2(5+7)=34 | | 3m+6n+2m-6n= |

Equations solver categories